BURCH-SCHNEIDER CAGE FRACTURE: A CASE REPORT - Gallo, Jiri; Florschutz, Anthony V. (Biomedical papers, 2005)
In this report, we present the case of a 64-year-old woman who sustained a Burch-Schneider cage fracture. Prior to this event, she underwent repeated acetabular reconstructions, but in the end prosthesis removal was performed as a salvage procedure. We believe that the primary cause of the fracture was metal fatigue facilitated by intraoperative re-contouring of the flange, as well as reuse of the cage. Based on this case we caution against repetitive or excessive flange bending during implantation of Burch-Schneider cages and do not recommend their reuse.
Keywords: Burch-Schneider anti-protrusio cage/Fracture/Revision hip arthroplasty/Fatigue failure/Balgrist cup